Pivot Subtitling on Netflix: The Case of Squid Game - Dallı, Harun (Journal of Audiovisual Translation, 2024)
This study examines the impact of English as a pivot language in the Turkish subtitles of Squid Game. As an integral part of global media, pivot subtitling (indirect subtitle translation) should not be understood as a response to an alleged talent crunch of subtitling professionals but rather as a deliberate policy and strategy pursued by streaming services and their language service providers to streamline subtitling workflows between non-English language pairs. The present research uncovers the multilingual nature of this practice and exposes its limitations through a case study of the Turkish subtitles of Squid Game. The findings suggest that English as a pivot language may have limitations in conveying the full range of sociopragmatic aspects present in the Korean discourse. This has implications for the social dynamics between the characters and the thematic undertones of the series. Beyond its function as a pivot language, English also serves as a dominant cultural filter that mediates Korean culture into downstream languages through an Anglo‑American lens, which may obscure the stratified facets of Korean and impose an added layer of cultural interpretation on target viewers. Lay summary When you kick back to watch the latest trending show, you may notice more non-English content topping the charts. That’s likely how you found Squid Game, which became the most-watched show in 94 countries. Like many others, you probably used subtitles in your local language to follow along because not everyone speaks Korean, right? But here’s the catch: the subtitlers of the show do not speak Korean either! Instead, they used English as a “pivot” language - meaning that the Korean dialogue was first translated into English, and then into your language. This practice is common in the industry to speed up translation due to an alleged shortage of subtitlers who can translate between non-English language combinations, like Korean and Turkish. But why should you care? Think about it. The creator of Squid Game spent 12 years bringing his vision to life. However, when going global, subtitles are just a necessary evil in the post-production stage. A step that has to be ticked, rather than a communicative goal to be achieved. If you use social media, you might have seen debates about the English subtitles of Squid Game. Now, imagine the situation for other languages. Using English as a bridge can dilute or alter important cultural and linguistic elements. For instance, when English is used as a middle step, certain Korean nuances might not fully come through in the Turkish subtitles. This can change how viewers understand the characters and the deeper themes of the series. My research highlights the need to rethink how we handle multilingual translations so that viewers worldwide can experience shows as they were truly meant to be understood. So, the next time you settle in for a binge-watch, know that you’re in good hands.